2013
DOI: 10.3748/wjg.v19.i8.1247
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of colorectal cancer testing using the California Health Inventory Survey

Abstract: Using CHIS we identified California citizens most likely to undergo colon cancer testing. The strongest variable associated with testing for all groups was physician recommendation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 27 publications
3
11
0
Order By: Relevance
“…Screening recommendations given by Western medical doctors significantly increased patient CRC screening (27,28). An analysis of the 2009 California Health Interview Survey with 30,857 respondents reported that the strongest predictor for having received CRC screening in the past 5 years was physician recommendation (29). The findings in this study suggest that TCM providers may have a similar effect on screening behavior.…”
Section: Discussionmentioning
confidence: 99%
“…Screening recommendations given by Western medical doctors significantly increased patient CRC screening (27,28). An analysis of the 2009 California Health Interview Survey with 30,857 respondents reported that the strongest predictor for having received CRC screening in the past 5 years was physician recommendation (29). The findings in this study suggest that TCM providers may have a similar effect on screening behavior.…”
Section: Discussionmentioning
confidence: 99%
“…12 Regrettably, though colon cancer screening and investigative technologies have begun to proliferate, one out of every five Americans with colon cancer has stage IV disease at the time of their diagnosis. 35 Many people with such late stage disease that has typically metastasised to the liver or lungs could benefit greatly from palliative chemotherapy. Synthetic randomised trial-based evidence has demonstrated its comforting as well as modest survival-enhancing effects, but it seems that only about half of those people with distally metastasised colon cancer in the USA ever receive such palliative care.…”
Section: Introductionmentioning
confidence: 99%
“…However, several studies have reported lower healthcare utilization and lower satisfaction among patients with longer travel times to healthcare facilities [16,30]. Therefore, healthcare strategies that ensure adequate availability of trained medical professionals and hospitals or that provide local referral centers within neighborhoods could significantly improve CRC outcomes in White communities [10,15,24]. Recent changes to the healthcare landscape in the U.S. associated with the Affordable Care Act (ACA) may provide a unique opportunity to develop healthcare policies designed to improve health outcomes and reduce health disparities.…”
Section: Discussionmentioning
confidence: 99%